Improving The Social Emotional Aspect Of Children Through Outbound Water Transfer Activities - Khulusinniyah Khulusinniyah; Maflaha Maflaha (Buana Pendidikan, 2023)
Early childhood education is preschool education that provides children with multiple stimulations to ensure optimal growth, development, and school readiness. One component of growth that must be encouraged is social-emotional development. In this study, classroom action research was used to address the issues discovered in the child's social-emotional development. Outbound is an activity that may actively include children in activities so that they can interact with their peers, establish collaboration, accomplish their obligations and responsibilities, and carry out these activities gladly and pleasantly. Children who can develop positive relationships and collaboration will grow into adults with high emotional intelligence. The study's findings revealed that children's social and emotional development increased during the pre-cycle, cycle I, and cycle II. Based on various assessment markers in the study, this demonstrates that outbound transfer of water can boost children's social and emotional development.